Chemical Vapor Deposition Growth of BN Thin Films Using B2H6 and NH3. Issue 2 (11th September 2019) - Yamada, Hisashi; Inotsume, Sho; Kumagai, Naoto; Yamada, Toshikazu; Shimizu, Mitsuaki
Abstract : The use of chemical vapor deposition (CVD) for the growth of BN thin films on Al2 O3 substrates using B2 H6 and NH3 is investigated. The simultaneous supply of B2 H6 and NH3 at a growth temperature of 1360 °C under a pressure of 100 mbar results in a rough surface, indicating 3D island growth, regardless of the V/III ratio. Furthermore, a significant decrease in growth rate is observed at high V/III ratios, owing to parasitic reactions between the B2 H6 and NH3 sources. In contrast, alternating the supply of B2 H6 and NH3 results in BN films with honeycomb‐like wrinkle patterns. The X‐ray diffraction peak intensities from the (002) and (004) planes of hexagonal boron nitride ( h ‐BN) increase as the number of supply cycles is increased. The BN film deposited with 1000 supply cycles shows a Raman shift at 1369 cm −1 with a full width at half maximum of 20 cm −1, corresponding to the first‐order E2g symmetry vibrational mode in h ‐BN. Abstract : The chemical vapor deposition for the growth of BN thin films on Al2 O3 substrates using B2 H6 and NH3 is investigated. Hexagonal BN films with honeycomb‐like wrinkle patterns are observed. The BN film shows a Raman shift at 1369 cm −1 with a full width at half maximum of 20 cm −1, corresponding to the first‐order E2g symmetry vibrational mode in h ‐BN.